(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
Higher education institutions are budgetary organizations with the highest possibility of forming extra-budgetary funds, and the direction and types of their activities are somewhat flexible to the requirements of the market economy. Funds of the payment-contract form are the largest source of financing in the activities of higher education institutions. For this reason, it is necessary to separately study the issue of financing the activities of higher education institutions at the expense of payment-contract funds and keeping their accounts. This article describes the theoretical-methodical basis of the generation of income from payment-contract form funds and their accounting in higher education institutions. The current state of income accounting of higher education institutions on payment-contract form funds was studied, the existing controversial situations were researched, and scientific proposals and practical recommendations for improvement were developed.